2019
DOI: 10.1029/2019wr024871
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic Groundwater Drawdown Along Crustal Ruptures During the 2016 Mw 7.0 Kumamoto Earthquake

Abstract: Groundwater‐level changes after earthquakes provide insight into changes in hydrogeological properties such as permeability and pore pressure. Quantifying such changes, both their location and magnitude, is usually hindered by limited data. Using extensive high‐resolution water‐level monitoring records, we provide direct evidence of significant groundwater drawdown (4.74‐m maximum) over a 160‐km2 area along crustal ruptures after the Mw 7.0, 2016, Kumamoto earthquake. Approximately 106 m3 of water disappeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 52 publications
4
74
0
Order By: Relevance
“…As reported by Mohr et al [12], discharge increases after earthquakes, observed mainly on stream gauges, can be explained by three mechanisms: (i) changes in static strain determining aquifer geometry modifications, pore pressure changes and consequent variations of hydraulic gradient i [3]; (ii) dynamic strain effects such as consolidation and shaking of water out of the unsaturated zone [5][6][7][8]14]; (iii) increased permeability due to dynamic strain [4,9,11,12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Mohr et al [12], discharge increases after earthquakes, observed mainly on stream gauges, can be explained by three mechanisms: (i) changes in static strain determining aquifer geometry modifications, pore pressure changes and consequent variations of hydraulic gradient i [3]; (ii) dynamic strain effects such as consolidation and shaking of water out of the unsaturated zone [5][6][7][8]14]; (iii) increased permeability due to dynamic strain [4,9,11,12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…7). Hosono et al (2019) also reported both of co-seismic rises and drops in groundwater level. However, large seasonal changes, which were probably induced mainly by precipitation, were recognized at e:SOY, f:SOI, g:YSM, h:SMR, and k:DMZ.…”
Section: Spring Watermentioning
confidence: 90%
“…However, large seasonal changes, which were probably induced mainly by precipitation, were recognized at e:SOY, f:SOI, g:YSM, h:SMR, and k:DMZ. Our sampling interval was much longer than that of Hosono et al (2019). Therefore, the postseismic flow rate changes in Fig.…”
Section: Spring Watermentioning
confidence: 99%
See 2 more Smart Citations